Sheep production, plant growth and nutritive value of a saltbush-based pasture system subject to rotational grazing or set stocking - Norman, H.C.; Wilmot, M.G.; Thomas, D.T.; Barrett-Lennard, E.G.; Masters, D.G. (Small ruminant research, 2010)
Saltbush ( Atriplex spp.) pastures are utilised by farmers in the Mediterranean-climate zones of Australia as maintenance feed for livestock during the autumn feed gap. The pastures are generally managed by set stocking at relatively low grazing pressures, allowing animals to choose their diet from the saltbush and understorey species on offer. Intensifying the grazing management of saltbush-based pastures may improve the long-term nutritional status of sheep by limiting the opportunity to selectively overgraze components of the diet which can lead to an inability to select a balanced diet in the future. The primary hypothesis investigated in this experiment was that rotational grazing of saltbush-based saline pastures will (a) increase sheep productivity per hectare (both liveweight gain and wool production) over set stocking, and (b) reduce the pattern of rapid liveweight gain/liveweight loss during autumn. An additional hypothesis was that the intake of saltbush, as a proportion of the total diet, will be negatively correlated to the digestibility of the understorey sward. To test these hypotheses two adjacent, 26 ha saltbush-based pastures were grazed with seven 6-month-old Merino sheep/ha for 250 days from early March (start of autumn) until mid November (spring). One paddock was set stocked while the other was divided into 10 subplots of 2.6 ha and rotationally grazed. Liveweight change, condition score, wool growth, biomass production and nutritive value of the pastures were measured on a fortnightly basis. Diet selection was estimated using carbon isotopes in faeces and pasture. The saltbush-based pastures, consisting of wide spaced rows of saltbush with a sown legume understorey were capable of supporting 7 growing sheep/ha for over 8 months of the year on mildly saline land in the low rainfall wheat belt of Western Australia (330 mm annual rainfall). We found that the differences between the flocks managed by rotational grazing or set stocking were relatively small (3.5 kg after 250 days of grazing and wool of marginally higher value) and it is unclear if rotational grazing would be justified given the higher labour and infrastructure inputs required. The proportion of saltbush selected by sheep reflected the quality of the saltbush and understorey. In autumn, when the saltbush and understorey had similar organic matter digestibility, the sheep managed to maintain liveweight by selecting a diet of approximately half of each component. In spring, when the understorey was highly digestible and in plentiful supply, the sheep still included an average of 13% saltbush in their diets. The growth rate of old man saltbush ( Atriplex nummularia) edible dry matter ranged from 0.29 to 3.43 kg/ha day (or 0.45–5.27 g/shrub day).